Multiline treatment of primary cutaneous adenoid cystic carcinoma with multiple metastases: a case report and literature review - Geng, Xiaotao; Sun, Daqing; Sun, Huimin; Zhang, Chunyan; Li, Jianwen; Hao, Furong; Chang, Xiaolong (Frontiers in Oncology, 2025)
BackgroundPrimary cutaneous adenoid cystic carcinoma (PCACC) is an extremely rare malignancy, typically presenting as a slow-growing, painless cutaneous mass with a relatively favorable prognosis compared to adenoid cystic carcinomas (ACC) of salivary gland origin. Metastatic PCACC is uncommon, with stage IV disease accounting for approximately 4% of reported cases. Due to its rarity, clinical understanding of the disease course and optimal management strategies remains limited.Case presentationWe report the case of a 57-year-old male who presented with a painful ulcerated mass on the left ankle. Magnetic resonance imaging (MRI) revealed a subcutaneous lesion, and histopathological examination following surgical excision confirmed the diagnosis of ACC. Immunohistochemistry was consistent with ACC, and a PET-CT scan excluded regional or distant disease, supporting the diagnosis of PCACC. The patient subsequently underwent adjuvant radiotherapy. However, within eight months, follow-up imaging revealed pulmonary and osseous metastases. A biopsy confirmed metastatic ACC consistent with the primary lesion. The patient was treated sequentially with three lines of systemic therapy, including chemotherapy, immunotherapy, and targeted therapy, along with palliative radiotherapy. Despite temporary disease stabilization, the malignancy progressed rapidly, with new pulmonary, intracranial, and extensive skeletal metastases. The patient eventually discontinued treatment and was lost to follow-up.ConclusionThis case highlights an unusually aggressive clinical course of PCACC with rapid progression to widespread metastatic disease shortly after definitive local treatment. Given the rarity of metastatic PCACC, this report contributes valuable insight into its natural history, diagnostic approach, and therapeutic challenges. It underscores the need for heightened clinical awareness and further research into effective systemic treatment strategies for advanced PCACC.